2001
DOI: 10.1103/physrevlett.87.224501
|View full text |Cite
|
Sign up to set email alerts
|

Gluing Bifurcations in a Dynamically Complicated Extended Flow

Abstract: We report the results of the first experimental study of imperfect gluing bifurcations in an extended fluid flow. It is shown that the central features of the theory are robust and are appropriate to describe the dynamics of a nontrivial physical system. The results include the first experimental evidence for a route to chaos which is an essential part of the theory of imperfect gluing bifurcations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…12 The low-dimensional dynamics observed in neighboring ranges of Re are organized through the underlying steady solution structure via Silnikov dynamics as shown by Mullin and Price. 13 More recently, Abshagen, Pfister, and Mullin 14 have shown that gluing bifurcations resulting from Z 2 symmetry broken states are important over a much wider range of parameter space than had previously been appreciated. An explanation of the dynamics which can arise at gluing bifurcations is given by Glendinning, Abshagen, and Mullin.…”
Section: Introductionmentioning
confidence: 99%
“…12 The low-dimensional dynamics observed in neighboring ranges of Re are organized through the underlying steady solution structure via Silnikov dynamics as shown by Mullin and Price. 13 More recently, Abshagen, Pfister, and Mullin 14 have shown that gluing bifurcations resulting from Z 2 symmetry broken states are important over a much wider range of parameter space than had previously been appreciated. An explanation of the dynamics which can arise at gluing bifurcations is given by Glendinning, Abshagen, and Mullin.…”
Section: Introductionmentioning
confidence: 99%
“…They arise from the merging of a period orbit with a saddle-point if a control parameter is varied and originate in the underlying local bifurcation structure of a nonlinear dynamical system [5]. Examples of homoclinic orbits can be found in many nonlinear physical systems, like, e.g., lasers [6], chemical oscillators [7], electronic circuits [8], and fluid flows [9][10][11][12][13]. In order to understand the organization of the bifurcation structure of a spatial extended nonlinear system an in-depth knowledge of the properties of the first bifurcation from the basic state is crucial [1].…”
mentioning
confidence: 99%
“…Examples arise from both imperfect local and imperfect global bifurcations in fluid flows with reflection symmetry (see, e.g., [3,9]). …”
mentioning
confidence: 99%
“…As a result the bifurcations from relative equilibria can be analysed in two steps, describing first the bifurcations associated with the orthogonal dynamics, and then adding the corresponding drift along the rotating wave (Krupa 1990). Subsequent instabilities of rotating waves to quasiperiodic flows have been explored experimentally and found to lead to a multitude of very-low-frequency states via a variety of global bifurcations, the details depending on all three governing parameters (Gerdts et al 1994;von Stamm et al 1996;Abshagen, Pfister & Mullin 2001;Abshagen et al 2005).…”
Section: Introductionmentioning
confidence: 99%